Faculty Senate, Agenda, March 20, 2008 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2008)
Valdosta State University. Faculty Senate, Agenda, March 20, 2008.
1 electronic document. Faculty Senate, Agenda, March 20, 2008. 27 pages. 456,068 bytes.
Keywords: Valdosta State University. Faculty Senate; Electronic records; Committees; Corporation reports